2017
DOI: 10.1177/1528083717699368
|View full text |Cite
|
Sign up to set email alerts
|

Conductive polymers for smart textile applications

Abstract: Smart textiles are fabrics able to sense external conditions or stimuli, to respond and adapt behaviour to them in an intelligent way and present a challenge in several fields today such as health, sport, automotive and aerospace. Electrically conductive textiles include conductive fibres, yarns, fabrics, and final products made from them. Often they are prerequisite to functioning smart textiles, and their quality determines durability, launderability, reusability and fibrous performances of smart textiles. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(118 citation statements)
references
References 65 publications
(155 reference statements)
0
117
0
1
Order By: Relevance
“…Conductive polymers and their composites have attracted much attention due to their outstanding characteristics, such as light weight, low cost, recyclability, and excellent electrical conductivity and chemical stability. Recent advancements in wearable smart devices have brought great convenience to human life . Devices such as touch screen displays, health monitoring sensors, functional clothing and other smart textile products all rely on the excellent electrical and mechanical properties of conductive polymers materials.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymers and their composites have attracted much attention due to their outstanding characteristics, such as light weight, low cost, recyclability, and excellent electrical conductivity and chemical stability. Recent advancements in wearable smart devices have brought great convenience to human life . Devices such as touch screen displays, health monitoring sensors, functional clothing and other smart textile products all rely on the excellent electrical and mechanical properties of conductive polymers materials.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons is the fact that wearable textronic prototypes suffer from poor washability and reliability [3]. The need to study the impact of the washing process on textronics was underlined back in 2004 [4] and it is all the more relevant that smart textiles are on the edge of being commercialized [5]. However, few research papers have tackled this particular issue until now, although it can be noted that the washability aspect of recent developments is more clearly taken into account [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The peak of the pure Fe3O4 nanoparticles appear at 475 cm -1 and 694 cm -1 is assigned to the Fe-O stretching vibration [13,14]. It is equally observed that the characteristic peak of PANI/F3O4 nanocomposites appeared at 3322 cm -1 (N-H stretching), 1517 cm -1 , 1545 cm -1 (C=C vibration stretching and deformation of benzenoid ring and quinoid respectively) [20,21]. At peak 1308 cm -1 represent for (C-N vibrating stretching of aromatic secondary amine), 1118 cm -1 as well as 900-800 cm -1 assigned for (C-N are out of plane deformation in 1,4-distributed benzene ring) which signified the presence of PANI contain Fe3O4 nanoparticles [13,22].…”
Section: Resultsmentioning
confidence: 99%